1998
DOI: 10.1142/s0129183198001266
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Hydrodynamics Formulation for Multiphase Flow Lattice-Boltzmann Models

Abstract: Lattice-Boltzmann (LB) models provide a systematic formulation of effective-field computational approaches to the calculation of multiphase flow by replacing the mathematical surface of separation between the vapor and liquid with a thin transition region, across which all magnitudes change continuously. Many existing multiphase models of this sort do not satisfy the rigorous hydrodynamic constitutive laws. Here, we extend the two-dimensional, seven-speed Swift et al. LB model1 to rectangular grids (nine speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 9 publications
1
85
0
1
Order By: Relevance
“…al. [2,3,4,5] developed an algorithm based on implementing a pressure tensor and Shan et al [6,7,8] developed an algorithm based on mimicking microscopic interactions. These algorithms have been succesfully applied to simulations of phase-separation [9], drop-collisions [1,10], wetting dynamics and spreading [11], and the study of dynamic contact angles [12,13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…al. [2,3,4,5] developed an algorithm based on implementing a pressure tensor and Shan et al [6,7,8] developed an algorithm based on mimicking microscopic interactions. These algorithms have been succesfully applied to simulations of phase-separation [9], drop-collisions [1,10], wetting dynamics and spreading [11], and the study of dynamic contact angles [12,13,14].…”
mentioning
confidence: 99%
“…and Π = ρu 2 + P + νu∂ x ρ [3,15] where ν = (τ − 0.5)/3. To second order the resulting equations of motion are, as usual, the continuity equation…”
mentioning
confidence: 99%
“…(6) and is not Galilean invariant. Holdych et al showed that the addition of this term led any nonGalilean invariant terms to be of the same order as nite lattice corrections to the Navier-Stokes equations [47]. In order to fully constrain the coe cients, a fourth condition is needed, which is [44] The pressure tensor can be de ned as [48]:…”
Section: Simulation Methodsmentioning
confidence: 99%
“…43 However, with thermal fluctuations present, density fluctuates locally (δρ = 0, but still small) and, therefore, the bulk viscosity coefficient is relevant. Previous LB studies 20,25,26,[29][30][31] incorporating noise have assumed the speed of sound squared v 2 s = v 2 c /3, a choice which zeroes the viscosity coefficient of the ∂ γ u γ term in Eq.…”
Section: B Thermal Noise In the Lattice-boltzmann Modelmentioning
confidence: 99%
“…We note that calculation of P αβ (x, n) must take into account corrections to reduce errors in non-Galilean invariant terms as presented in Ref. 43.…”
Section: Appendix A: Details For the D3q15 Latticementioning
confidence: 99%